1981
DOI: 10.1159/000299659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Routine Administration of Folic Acid and Iron during Pregnancy

Abstract: Haematological and folic acid status were assessed in 200 women in the 6th month of pregnancy. Folic acid deficiencies with no or little haematological impairment were found in one third of the cases, and their occurrence increased when the socioeconomic level was low. During the last trimester of pregnancy, the women were given either iron alone or iron and folic acid supplementation. In the mothers, the rise of folate values in serum and red blood cells, in the folic acid-supplemented group, had no obvious h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…It was observed that higher maternal folate concentrations during late pregnancy had no benefit for reducing the risk of SGA in a multiethnic Asian population [26]. If there is an effect of FA supplementation during pregnancy on SGA, it may possibly only be observed in the face of more generalized maternal folate depletion [27]. …”
Section: Discussionmentioning
confidence: 99%
“…It was observed that higher maternal folate concentrations during late pregnancy had no benefit for reducing the risk of SGA in a multiethnic Asian population [26]. If there is an effect of FA supplementation during pregnancy on SGA, it may possibly only be observed in the face of more generalized maternal folate depletion [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Blotet al [14] report that more than one third of the women after 6 months of pregnancy or at delivery exhibit plasma folate levels below normal. However, Hall et al [15], in a study of a complete antenatal population, suggest that the fall in serum folate level that occurs in normal pregnancy is due mainly to plasma volume expansion and should be regarded as physiologic.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has been noted that about 8% of pregnant women need permanent drug treatment due to various chronic disease and pregnancy induced complications. 6 But unfortunately due to easy availability of drugs coupled with inadequate health services, increased proportions of drugs are used as selfmedications, as compared to the prescribed drugs which lead to adverse drug reactions and drug interactions during pregnancy.…”
Section: Introductionmentioning
confidence: 99%